The Effect of Innovation Climate and Collaborative Learning on the Performance of Elementary School Teachers at Kelapa Dua District Tangerang Regency - Mariyanto; Sudadio; M Syadeli Hanafi (Yayasan Payungi Smart Madani, 2025)
The study aims to describe the influence of Innovation Climate and Collaborative Learning on the Performance of Elementary School Teachers in Kelapa Dua District in Tangerang Regency. The study used an explanatory method with a quantitative approach. The research instrument used a closed questionnaire on 74 respondents using a total sampling technique. The study used simple and multiple linear regression techniques to test the influence of independent variables on dependent variables using SPSS 26. The results of the study showed that: (1) Innovation climate has a positive and significant influence on teacher performance. This is indicated by a regression coefficient of 0.532 and a significance value of 0.000 (<0.05), with a regression equation of Y = 33.807 + 0.532X1. (2) Collaborative learning has a positive and significant influence on teacher performance. The regression coefficient obtained was 0.336 with a significance value of 0.000 (<0.05), and a regression equation of Y = 42.144 + 0.336X2. (3) Innovation climate and collaborative learning simultaneously have a positive and significant influence on teacher performance. This is proven by the calculated F value of 22.319 which is greater than the F table of 2.733 and a significance value of 0.000 (<0.05). The multiple regression equation obtained is Y = 22.823 + 0.443X1 + 0.214X2. The coefficient of determination value is 0.369. This means that the magnitude of the influence of innovation climate and collaborative learning on teacher performance is 36.9% while the remaining 63.1% is influenced by other factors not studied by the researcher. The novelty of this study lies in the integration of innovation climate and collaborative learning variables in one predictive model of elementary school teacher performance in the context of implementing the Independent Curriculum, which has rarely been studied simultaneously in previous studies in Tangerang Regency.